2007
DOI: 10.1063/1.2775093
|View full text |Cite
|
Sign up to set email alerts
|

Guided wave propagation in 0.67Pb(Mg1∕3Nb2∕3)O3–0.33PbTiO3 single crystal plate poled along [001]c

Abstract: Dispersion relations of Lamb waves and shear horizontal (SH) waves propagating in the [100] and [110] directions of 0.67Pb(Mg1∕3Nb2∕3)O3–0.33PbTiO3 piezoelectric single crystal plate poled along [001]c were calculated. Multiple crossings between symmetric and antisymmetric modes appear due to the moderate anisotropy of these crystals. As frequency increases, the velocities for SH wave modes approach 2.88 and 0.88mm∕μs, respectively, for waves propagating along [100] and [110] directions. These limiting velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Such acoustic guided waves propagating in plates can be decoupled into two kinds of waves, namely, shear horizontal (SH) waves and Lamb waves, while Lamb waves can be further divided into symmetric and antisymmetric modes. The zero th order symmetric mode (S 0 ) and antisymmetric mode (A 0 ) Lamb waves are the most useful ones [334,335]. Partial wave theory is the most commonly used method for analyzing harmonic wave propagation in anisotropic materials [336,337,338].…”
Section: Acoustic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such acoustic guided waves propagating in plates can be decoupled into two kinds of waves, namely, shear horizontal (SH) waves and Lamb waves, while Lamb waves can be further divided into symmetric and antisymmetric modes. The zero th order symmetric mode (S 0 ) and antisymmetric mode (A 0 ) Lamb waves are the most useful ones [334,335]. Partial wave theory is the most commonly used method for analyzing harmonic wave propagation in anisotropic materials [336,337,338].…”
Section: Acoustic Propertiesmentioning
confidence: 99%
“…Guided waves propagating along (a) [100] c and (b) [110] c of [001] c poled PMN-33%PT crystal plates for short circuit case [335]. …”
Section: Figmentioning
confidence: 99%
“…Dispersion curves for Lamb waves in a ferroelectric single crystal plate were plotted in ref. [28]. Propagation of piezoelectric TT waves through a joint of two semi-infinite ceramic plates was obtained in ref.…”
Section: Wave Propagationmentioning
confidence: 99%
“…But guided wave propagation in PMN-PT single crystals has not been studied in depth. Our previous studies showed complex entangled dispersion relations and other interesting characteristics of guided waves [14,15]. In this paper, the displacements of symmetric and antisymmetric modes of Lamb and SH waves have been studied in detail.…”
Section: Introductionmentioning
confidence: 98%